2014
DOI: 10.1037/prj0000080
|View full text |Cite
|
Sign up to set email alerts
|

Assessing an Internet-based parenting intervention for mothers with a serious mental illness: A randomized controlled trial.

Abstract: This RCT establishes that mothers with a SMI are interested in and capable of receiving online parenting education and support. Findings demonstrate that an online parenting intervention can improve parenting and coping skills and decrease parental stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
60
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(60 citation statements)
references
References 35 publications
0
60
0
Order By: Relevance
“…Many of these interventions were web-based and involved education, developing coping skills, and providing social support. For example, two online education interventions focused on developing parenting skills for parents with SMI (Jones et al, 2014; Kaplan et al, 2014), while four online interventions included a peer component such as peer-to-peer online social networking (Alvarez-Jimenez et al, 2013; Gleeson et al, 2014), peer support (Kaplan et al, 2011), or peer coaching (Simon et al, 2011). One study focused on promoting physical activity using wearable activity tracking devices linked to smartphones (Naslund et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Many of these interventions were web-based and involved education, developing coping skills, and providing social support. For example, two online education interventions focused on developing parenting skills for parents with SMI (Jones et al, 2014; Kaplan et al, 2014), while four online interventions included a peer component such as peer-to-peer online social networking (Alvarez-Jimenez et al, 2013; Gleeson et al, 2014), peer support (Kaplan et al, 2011), or peer coaching (Simon et al, 2011). One study focused on promoting physical activity using wearable activity tracking devices linked to smartphones (Naslund et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…Supported online psychological interventions can improve clinical outcomes in mothers with postnatal depression (Kaplan, Solomon, Salzer, & Brusilovskiy, 2014; O'Mahen et al., 2014) and parenting in parents with and without mental health problems (Love et al., 2016; Sanders, Baker, & Turner, 2012; Sanders, Dittman, Farruggia, & Keown, 2014). Additionally, three studies of online Triple P indicated child behaviour improvements (Love et al., 2016; Sanders et al., 2012; Sanders, Dittman et al., 2014).…”
Section: Introductionmentioning
confidence: 99%
“…These most often focus on psychoeducation to enhance children's knowledge about PMI and strengthening children's resilience, 13 or on educating parents about the impact of mental illness on families and improving their parenting skills. 5 While there is evidence that many of these interventions can be helpful ,2, 5, 13 they are usually aimed at parents or children, as opposed to whole families, and they don't directly address how family members talk with each other about PMI.…”
Section: Introductionmentioning
confidence: 99%
“…• A more negative and confrontational family environment and poorer parent-child relationships; [3][4][5][6] • The burden for children of having to care for an ill parent; 7,8 • Children's concerns about the wellbeing of their parent or about potential family breakdown; 9 and, • Children's lack of understanding of PMI and how it can affect their parent. This can include confusion, self-blame, and anxieties about their own mental health and the possibility of "catching" mental illness like a cold.…”
Section: Introductionmentioning
confidence: 99%